Effect Of Additional Probiotic In Cattle Feed On Cattle's Consumption And Growth Rate - Lingga, Rahmad; Puji Astuti, Rufti; Ilham Bahtera, Novyandra; Adibrata, Sudirman; Nurjannah, Nurjannah; Ahsaniyah, Shinta; Fatansyah, Firzan; Irawati, Irawati (International Journal of Science, Technology & Management, 2022)
This study aimed to determine the level of feed consumption, weight gain of cattle, and to calculate the population of lactic acid bacteria (LAB) and pathogenic bacteria Escherichia coli and Salmonella in cattle feces in order to determine the effect of giving probiotics on the digestive system of cattle. The research object used was 10 bali cattle with a weight of about 90-120 kg. The data in this study were analyzed by experimental design using analysis of variance to determine the effect of giving probiotics to cattle feed on cattle weight gain. The treatment in question includes G0 with treatment in the form of feeding with a composition of 60% forage, 15% palm cake, 25% cassava, and 100 ml molasses. Meanwhile, G1 was treated with the same feed as G0, but added with 100 ml of probiotic Probio_FM. Based on the results of the study, it is known that probiotics given to cattle feed showed no significant effect on the level of feed consumption and body weight of cattle where cattle with non-probiotic feed had a higher average consumption level than cattle on probiotic feed. Furthermore, this causeed the average weight gain of non-probiotic cattle to be higher than that of probiotic cattle. In addition, it was known that the population of Lactic Acid Bacteria in the feces of probiotic cattle showed a higher number of LAB colonies compared to non-probiotic cattle with numeric values of 3.6x108, 3.3x109, and 2.7x1010. This proved that giving probiotics to bali cattle with a concentration of 100 ml / 100 kg of feed was able to increase the concentration of lactic acid bacteria in the digestive system.